IMPLEMENTASI KEBIJAKAN IDENTITAS KEPENDUDUKAN DIGITAL DI KABUPATEN SUMEDANG - Suherman; Agustin, Agi; Lestari, Elsa Sandra; Muslimah, Fatimah Situ; Hidayat, Teuku Rizki; Maulana, Yogie Sidiq (JRPA - Journal of Regional Public Administration, 2023)
This research was conducted to analyze the implementation of the Digital Identity policy in Sumedang Regency. Not only about the implementation but also analyzing the inhibiting factors and efforts to overcome obstacles in implementing the digital population identity policy in Sumedang Regency. the research method used is qualitative with data collection techniques consisting of literature study and field study. While data processing is done through data reduction, data presentation, and conclusion drawing. The research informants were employees of the Population and Civil Registration Office of Sumedang Regency where the determination of informants used purposive sampling techniques. The results showed that the implementation of the digital population identity policy in Sumedang Regency can be said to be quite good because it can be seen from the information from several sources shared with researchers that employees always try to do as much service as possible so that the service is satisfactory for department employees and ASN. Factors that hinder implementation are the competence of service officers and the quality of service supporting facilities and infrastructure.